2018
DOI: 10.1016/j.jweia.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Urban wind energy: Some views on potential and challenges

Abstract: Urban wind energy consists of the utilization of wind energy technology in applications to the urban and suburban built environment. The paper provides some views on the progress made recently in the areas of wind resource assessment in the urban habitat; the utilization of suitable wind turbines for enhancing the exploitation of these resources; and the significant role of knowledge of building and urban aerodynamics for an optimal arrangement of interfacing augmented wind with its extraction mechanisms. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(83 citation statements)
references
References 82 publications
1
81
0
1
Order By: Relevance
“…Stathopoulos et al [7], in their review of urban SWT technologies, argue that, although Vertical-Axis Wind Turbines (VAWTs) tend to be quieter and visually pleasant, the Horizontal-Axis Wind Turbines (HAWTs) remain a preferred choice for urban applications. This is because VAWTs remain commercially less cost-efficient than HAWTs.…”
Section: Small Wind Turbines-interest and Researchmentioning
confidence: 99%
“…Stathopoulos et al [7], in their review of urban SWT technologies, argue that, although Vertical-Axis Wind Turbines (VAWTs) tend to be quieter and visually pleasant, the Horizontal-Axis Wind Turbines (HAWTs) remain a preferred choice for urban applications. This is because VAWTs remain commercially less cost-efficient than HAWTs.…”
Section: Small Wind Turbines-interest and Researchmentioning
confidence: 99%
“…In the urban area the oscillating bodies or structures can be placed to harvest the energy where the wind velocities are relatively higher. Recently, Stathopoulos et al (2018) and Micallef and Bussel (2018) showed that the suitable places for the devices to install in the urban areas and harvest the energy from the wind.…”
Section: Tested In Wind Tunnelmentioning
confidence: 99%
“…Therefore, applying the local identity is one of the most important issues to protect the heritage village's features, conserve the local traditions, and investigate the village regarding historical tourism purposes. Furthermore, climatic conditions must be taken into account when designing the heritage village in order to employ the local natural resources, such as solar design, shading strategies (Ghosh andNeogi 2018, Luo, Li et al 2018), and urban wind energy to provide efficient natural ventilation for the heritage village ( Stathopoulos, Alrawashdeh et al 2018). The design of Al-Qahad heritage village must take into account the local climatic conditions and the original urban and architectural identity.…”
Section: Concept and Designmentioning
confidence: 99%